PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TPS UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA POKOK BAHASAN KELILING DAN LUAS LINGKARAN PADA SISWA KELAS VIIIB SEMESTER GENAP SMP NEGERI 2 AJUNG - USFURIYAH USFURIYAH (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2022)
So far, mathematics learning at SMP Negeri 2 Ajung applies the lecture and question and answer method. As a result, it is known that the average student learning outcomes are low, many are incomplete. To overcome this, the researchers did CAR by applying cooperative learning type TPS (Think, Pair, Share) on the circumference and area of ??a circle. This study aims (1) to determine whether the application of cooperative learning types can improve student learning outcomes. (2) To determine the percentage of learning completeness in the application of TPS type learning. The research subjects were students of class VIII B of SMP Negeri 2 Ajung totaling 26 students. This PTK was carried out for 2 cycles. Each cycle is carried out through the following stages: planning, implementation, observation and reflection at the end of the cycle. The results of the first cycle obtained 7 students (25.9%) completed learning while the students did not complete as many as 20 students (74.1%), with an average grade of 55.6. The results of the second cycle obtained 23 students (85.2%) completed learning while not completed there were 4 students (14.8%), with an average grade of 73.6. Based on the results of data analysis conducted by researchers, the percentage of student learning outcomes from cycle I to II increased by 59.3%. From these findings, Mathematics Learning with the TPS Model can improve student learning outcomes for class VIII B SMP Negeri 2 Ajung in the matter of calculating the circumference and area of ??a circle both classically and individually. ABSTRAKSelama ini pembelajaran matematika di SMP Negeri 2 Ajung menerapkan metode ceramah dan tanya jawab. Hasilnya PH diketahui rerata perolehan hasil belajar siswa rendah, banyak tidak tuntas. Untuk mengatasinya peneliti melakukan PTK dengan menerapkan pembelajaran kooperatif tipe TPS (Think, Pair, Share) pada materi Keliling dan Luas Lingkaran. Penelitian ini bertujuan (1) Untuk mengetahui apakah penerapan pembelajaran kooperatif tipe dapat meningkatkan hasil belajar siswa. (2) Untuk mengetahui persentase ketuntasan belajar pada penerapan pembelajaran tipe TPS. Subyek penelitian adalah siswa kelas VIII B SMP Negeri 2 Ajung berjumlah 26 siswa. PTK ini dilaksanakan selama 2 siklus. Tiap siklus dilaksanakan melalui tahapan sebagai berikut : perencanaan, pelaksanaan, Observasi dan refleksi pada akhir siklus. Hasil siklus 1 diperoleh 7 siswa (25,9 %) tuntas belajar sedangkan siswa tidak tuntas sebanyak 20 siswa (74,1%), dengan nilai rata-rata kelas 55,6. Hasil siklus 2 diperoleh 23 siswa (85,2 %) tuntas belajar sedangkan tidak tuntas ada 4 siswa (14,8 %), dengan nilai rata-rata kelas 73,6. Berdasarkan hasil analisis data yang dilakukan peneliti menunjukkan peningkatan persentase ketuntasan hasil belajar siswa dari siklus I ke II terjadi peningkatan sebesar 59,3 %. Dari temuan tersebut, Pembelajaran Matematika dengan Model TPS dapat meningkatkan hasil belajar siswa kelas VIII B SMP Negeri 2 Ajung pada materi menghitung keliling dan luas lingkaran baik secara klasikal maupun secara individu